Application of Plackett-Burman screening design to the modeling of grafted alginate-carrageenan beads for the immobilization of penicillin G acylase - Elnashar, Magdy; Wahba, M.; Amin, M.; Eldiwany, A. (2014)
Grafted alginate-carrageenan beads were used to immobilize the industrial enzyme penicillin G acylase (PGA). Sixteen factors were screened with the Plackett-Burman design (PBD) to test their significance on the gel beads formation and enzyme immobilization process. The results of PBD showed a wide variation of 30-fold in the amount of immobilized penicillin G acylase (iPGA) from 11.9 to 354.16 U/g of beads; this reflected the importance of the optimizing process. Among the 16 tested factors, only 3 were proven to be significant. These factors were the enzyme buffer pH (N), enzyme soaking time (Q) with the gel beads, and enzyme concentration (P). The Pareto chart revealed that both Q and P exerted significant positive effects on the amount of iPGA, whereas N had a negative effect. We recommend further study to optimize only these three significant, distinctive enzyme factors. The PGA covalent attachment to the gel beads were proven by Fourier transform infrared spectroscopy, elemental analysis, and NaCl and reusability tests. The best gel bead formula succeeded in the immobilization of 354.16 U/g of beads and proved to be reusable 14 times, retaining 84% of the initial enzyme activity. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40295. Copyright © 2013 Wiley Periodicals, Inc.